New data on the Lamut Suite age (the Algan mountains, the north-western part of the Koryak Highland) - T.N. Palechek; A.V. Moiseyev; M.Yu. Gushina (Вестник Камчатской региональной ассоциации "Учебно-научный центр". Серия: Науки о Земле, 2018)
This article presents new data obtained during the study of radiolarians and U-Pb dating of clastic zircons from sections of the Lamut suite, located in the upstream of the Oltyan River and the northern branch of Mount Pik (the Algan Mountains). For the first time radiolarians of the Campanian age were isolated. The analysis showed that in the Campanian age, in the north-western part of the Koryak Highlands, prunoid and diskoid forms dominated in the radiolarian fauna, which is typical for temperate cold-water basins. All samples collected from the Lamut suite contain P. articulatum that is the index-species for the Campanian interval in the boreal region. Data of U-Pb dating of zircon clastic grains indicate accumulation of sedimentary material in the post-Coniacian age and do not contradict the micropaleontological data.